KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS SRONDOL KECAMATAN BANYUMANIK - Fathon, Arsyad; Lestari, Hesti; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2015)
Health is an important thing in life to make a better life standard of human life. Many things can be done to increase people health, one of them is by health service implementation. Srondol district health center is an organizaation who give health service for people society. According to the study of health service quality, service quality is a level of superiority which wanted and controlling of those superiority level to fulfill patient’s desires. The result of this research indicates that Srondol district health center has been giving good health service to people, even there are still some of deficiency in some parts, Srondol district health center should increase the indicators of public service quality, especially in the comfort of buildings, parking area, and manner value and also the hospitality of the health officer in Srondol District health center Banyumanik Sub District Semarang City.